KARAKTERISTIK PASIEN DAN LUARAN FEMTO LASIK DI PMN RS MATA CICENDO - Budiman; Knoch, Andrew Maximilian Herman; Siagian, Helena Margareth Angelica (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2023)
Background: Refractive error ranks first among all other types of eye. However, there is currently no new research in Indonesia on the epidemiology of the most recent myopia patients or the results of Femto LASIK, which is one of the well-known refractive error remedies that the public is choosing these days. This study aimed to describe the characteristics and outcomes of patients who underwent Femto LASIK at the Cicendo National Eye Hospital throughout 2022. Methods: A retrospective descriptive study was conducted using medical records of patients who underwent Femto LASIK surgery in 2022. Gender, age, level of education, place of residence, eye lateralization, motives for surgery, presenting visual acuity, best corrected visual acuity, degree of myopia, and refractive error correction were reviewed. Results: A total of 209 patients were selected. The majority of the subjects were male (67,5%) with age ranging from 18 to 48 years. Most patients were high school graduates (84,2%) and resided in Java Island (48,8%). The surgery was predominantly performed on both eyes (88%) due to career requirements (60,3%) and for the correction of mild myopia (44,8%). Most patients presenting visual acuity were severe visual impairment (40,4%). After LASIK, there were residual refractive errors for all degrees of myopia. The efficacy and safety index were highest among cases of mild myopia. Conclusion: The study's conclusions showed that male residents of Java were the patients' most prevalent characteristics. Femto LASIK has proven to be highly effective and safe, particularly in cases of low myopia.